Triboelectric Nanogenerators Based on Melamine and Self‐Powered High‐Sensitive Sensors for Melamine Detection. (17th February 2016) - Zhu, Huarui; Wang, Ning; Xu, Ying; Chen, Shuwen; Willander, Magnus; Cao, Xia; Wang, Zhong Lin
Abstract : Melamine (Mel) is added illegally to foods and feeds due to its high nitrogen content and high intake, and it causes serious health problems, so it is urgent to build a simple and quick method for detecting Mel in our daily life. In this work, a self‐powered Mel detection method is developed that is based on the newly invented triboelectric nanogenerator (TENG) by using the strong electronegativity property of Mel. In addition, Mel can enhance the electrical output signals of the TENGs by pairing with other triboelectric materials. Thus a high‐sensitive Mel sensor is designed based on polytetrafluoethylene (PTFE) TENG; the output current of TENG increases with the addition of Mel, resulting in largely improved detection limit of Mel with 0.5 ppb and a linear increase range from 1 to 500 ppb. This study not only develops a new type of material for TENG, but also demonstrates an innovative and convenient method for the detection of Mel and other biomaterials. Abstract : A self‐powered sensor for the detection of melamine (Mel) is developed for the first time with a detection limit of 0.5 ppb and a linear increase range from 1 to 500 ppb. This system is capable of detecting other biomaterials based on the enhanced triboelectrification using triboelectric nanogenerator (TENG) without an external electrical source.